In situ nitridation of titanium-molybdenum alloys during laser deposition - Borkar, Tushar; Gopagoni, Sundeep; Nag, Soumya; Hwang, J. Y.; Collins, Peter C.; Banerjee, Rajarshi (SPRINGER, 2012)
In situ nitridation during laser deposition of titanium-molybdenum alloys from elemental powder blends has been achieved by introducing the reactive nitrogen gas during the deposition process. Thus, Ti-Mo-N alloys have been deposited using the laser engineered net shaping (LENSTM) process and resulted in the formation of a hard alpha(Ti,N) phase, exhibiting a dendritic morphology, distributed within a beta(Ti-Mo) matrix with fine scale transformed alpha precipitates. Varying the composition of the Ar + N-2 gas employed during laser deposition permits a systematic increase in the nitrogen content of the as-deposited Ti-Mo-N alloy. Interestingly, the addition of nitrogen, which stabilizes the alpha phase in Ti, changes the solidification pathway and the consequent sequence of phase evolution in these alloys. The nitrogen-enriched hcp alpha(Ti,N) phase has higher c/a ratio, exhibits an equiaxed morphology, and tends to form in clusters separated by ribs of the Mo-rich beta phase. The Ti-Mo-N alloys also exhibit a substantial enhancement in microhardness due to the formation of this alpha(Ti,N) phase, combining it with the desirable properties of the beta-Ti matrix, such as excellent ductility, toughness, and formability.
Keywords: COMPOSITES; COATINGS